Vol. 732 : Radiation from Relativistic Electrons in Periodic Structures (RREPS2015): XI International Symposium, 6–11 September 2015, Saint Petersburg, Russian Federation; [proceedings]; Journal of Physics: Conference Series (2016, 2016)
Title screen